Entrada: The Bowed Piano Ensemble - Scott, Stephen; Sanny, Tom; Scott, Amy (San Francisco, CA New Albion records Adigital music, 1999)
The Bowed Piano Ensemble, founded by Stephen Scott at Colorado College in 1977, has evolved into a small orchestra whose ten players conjure, from one open grand piano, long, singing lines, sustained drones, chugging accordion-like figures, crisp staccato tones reminiscent of clarinets, deep drum tones and more, often simultaneously, to create a rich, contrapuntal new-chamber-music tapestry. The Ensemble has made nine European tours and three to Australia. We have performed at world-renowned venues such as the Sydney Opera House, Jazz at Lincoln Center, Town Hall, Palais des Beaux Arts in Brussels, the medieval Town Hall in Tallinn, Estonia and Jameos del Agua, a volcanic lava-tube-become-concert-hall in Lanzarote, Canary Islands. The Ensemble has performed commissioned works with the Los Angeles Chamber Orchestra, Pacific Symphony, New York Philharmonic English horn soloist Thomas Stacy and the London ensemble Piano Circus. Our six recordings (three with soprano Victoria Hansen) are on the New Albion, Albany and Navona labels.